Late‐Summer Peak in Sediment Accumulation in Two Lakes with Contrasting Watersheds, Alaska. Issue 4 (15th October 2015) - Fortin, David; Kaufman, Darrell S.; Arnold, Megan; Schiefer, Erik; Hawley, Nathan
ABSTRACT: The timing of clastic sedimentation in two glacial‐fed lakes with contrasting watersheds was monitored using sequencing sediment traps for two consecutive years at Allison Lake (Chugach Range, Alaska) and four months at Shainin Lake (Brooks Range, Alaska). Shainin Lake is a weakly stratified lake fed by distant glaciers, whereas Allison Lake is more strongly stratified and fed predominantly by proximal glaciers. At Shainin Lake, sediment accumulation started in late June and reached its maximum in mid‐August, just before lake mixing and during a period of low river discharge. The grain size of the sediment reaching the sediment trap in Shainin Lake was homogenous throughout the summer. At Allison Lake, pulsed sedimentation of coarse particles during late summer and early fall storms were superimposed on the fine‐grained sedimentation pattern similar to that observed at Shainin Lake. These storms triggered underflows that were observed in the thermal structure of the lake and deposited abundant sediment. The sequencing sediment traps reveal a lag between fluvial discharge and sediment deposition at both lakes, implying limitations to interpreting intra‐annual sedimentary features in terms of inflow discharge.